Study of Cellulose-N,N'-Methylenebisacrylamide-Acrylic Acid as Pb2+ Ion Adsorbent - M. Suhartini; J. Ginting; S Sudirman; A.D. Putri; Z.R. Mubarak (Atom Indonesia, 2018)
Cellulose can be used as a metal ion adsorbent. However, it is specific to certain metal ions and has some drawbacks. To increase the capture of certain metal ions,cellulose needs to be modified. Cellulose modification was carried out using N, N'- methylenebisacrylamide (MBA) as crosslinking agent and acrylic acid (AA)          as grafting agent. Gamma rays from Cobalt-60 was used as the initiator by simultaneous irradiation method. The aim of this study is to improve and observe the capture ability of cellulose as Pb2+metal ion adsorbent. The characterization was performed by FTIR, DSC, SEM, and EDX. The thermal analysis and ion exchange capacity measurement showed that the resulting copolymer has a better thermal stability and ion exchange ability thanpure cellulose.The applications of the copolymer on Pb2+ ion adsorption indicated that the maximum adsorption is 99.8 % of 3 ppm Pb2+ ion sorbent at pH ≈ 7. SEM analysis showed that the copolymer is porous while pure cellulose appears fibrous. EDX Analysis showed Pb2+ metal ion adsorption by cellulose-MBA-AA.